Can district level support enhance coverage and equity? Evidence from India’s nutrition program - Gune, Soyra; Alderman, Harold; Avula, Rasmi; Nguyen, Phuong Hong; Dwivedi, Laxmikant; Kapur, Avani; Shukla, Ritwik; Pedgaonkar, Sarang; Singh, Shri Kant; Menon, Purnima; Chakrabarti, Suman (SSRN, 2025)
Importance: India’s Integrated Child Development Services (ICDS) program is among the world’s largest nutrition and health programs that offers services to pregnant, lactating mothers, and young children. To support national investments towards universalization of ICDS interventions, between 2016 and 2020, the Indian government in collaboration with multiple partners, introduced system strengthening mechanisms at the district (subnational administrative unit) level in 64% of India’s districts.